2007
DOI: 10.1038/sj.leu.2404874
|View full text |Cite
|
Sign up to set email alerts
|

Human telomerase is regulated by erythropoietin and transforming growth factor-β in human erythroid progenitor cells

Abstract: Telomerase catalytic subunit (hTERT) exerts important cellular functions including telomere homeostasis, genetic stability, cell survival and perhaps differentiation. However, the nature of external or internal signals, which regulate hTERT expression in tissues, remains poorly understood. Thus, whereas it has been described that hTERT gene is regulated along the differentiation of primitive myeloid progenitors, the effect of specific cytokines on telomerase expression in each myeloid lineage is currently unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…Next to RBC production, erythropoietin promotes telomerase activity in erythroid progenitor cells (Prade-Houdellier et al, 2007), supporting the relevance of TL maintenance in erythropoiesis. While erythropoietin levels were reported to increase in a healthy, aging population (Kario et al, 1991), at least in men, RBC levels decreased with age in the Asklepios population, suggesting that the reported association between RBC count and TL is independent of erythropoietin.…”
Section: Discussionmentioning
confidence: 77%
“…Next to RBC production, erythropoietin promotes telomerase activity in erythroid progenitor cells (Prade-Houdellier et al, 2007), supporting the relevance of TL maintenance in erythropoiesis. While erythropoietin levels were reported to increase in a healthy, aging population (Kario et al, 1991), at least in men, RBC levels decreased with age in the Asklepios population, suggesting that the reported association between RBC count and TL is independent of erythropoietin.…”
Section: Discussionmentioning
confidence: 77%
“…EPO can also differentiat mouse embryonic stem cells differentiate into cardiomyocytes (5, 7), and also interferes with differentiation of neural stem cells into neural cells (8,20). Following the deep research of EPO, it was found that hTERT mRNA transcription factor was regulated by EPO in vitro cultured erythroid progenitor cells (21). There were experimental results (22) showed that TERT mRNA expression was significantly up regulated in BM CD34…”
Section: Discussionmentioning
confidence: 99%
“…99 This paper suggests that enhanced SPOTLIGHT JAK2 activation may activate hTERT expression and thereby, enhance survival and increase erythroid differentiation of stem cells. 99 Finally, MPD progression to myelofibrosis appears to be associated with an increase in JAK2V617F-expressing HSC 90 as well as overproduction of osteoprotegerin (OPG), which is an essential mediator of osteoblast production. 100 Osteoblasts form an essential component of the HSC niche in the bone marrow microenvironment and thus, increased osteoblast production may enhance the survival of miscreant MPD stem cells returning to the marrow (Figure 1).…”
Section: Bcr-abl-negative Mpd Survivalmentioning
confidence: 97%
“…98 A recent report suggested that human telomerase reverse transcriptase (hTERT) known to be involved in regulating telomere length, genomic stability and cell survival may also play a role in EPO-induced red blood cell production. 99 EPO was shown to activate hTERT gene expression through a JAK2/STAT5/c-myc axis. 99 This paper suggests that enhanced SPOTLIGHT JAK2 activation may activate hTERT expression and thereby, enhance survival and increase erythroid differentiation of stem cells.…”
Section: Bcr-abl-negative Mpd Survivalmentioning
confidence: 99%
See 1 more Smart Citation